Factors Related to Health Resilience in Students Affected by Disaster at Campus Graha Ananda Palu - Sadli Syam; Muhammad Sabri Syahrir; Muhammad Aji Satria; Iin Irawati (Journal of Public Health and Pharmacy, 2025)
Introduction: Palu City, located in Central Sulawesi Province, is one of the most vulnerable areas disaster, intervention countermeasures disaster that has been This focus on intervention recovery source power and development infrastructure. while on intervention poor mental health get attention. Follow stages disaster in Palu City, when these are the people affected disaster in Palu City now currently in phase recovery going to resilience, namely restore normal condition and strengthen Power stand public to disaster. Research This aiming for inspect relationship preparedness, mental health and behavior health post disaster to resilience health of affected students disaster at the Institute Health Technology and Business Graha Ananda, Palu City, to be able to strengthen resilience health and able adapt to threat, danger, serious disturbance from disaster.